Clusters of neural cell adhesion molecule at sites of cell-cell contact (The Rockefeller University Press, 1992)
I have examined the distribution of neural cell adhesion molecule (N- CAM) in cultured C2 myogenic cells and other cell lines to determine if N-CAM accumulates at sites of cell-cell contact. C2 cells growing in log phase display large clusters of neural cell adhesion molecule where they contact each other. These clusters are remarkably stable, do not form at cell-substrate contacts, and appear not to be enriched in a number of other cytoskeletal, membrane, or extracellular proteins. Thus, N-CAM clusters form preferentially in response to cell-cell contact and are specifically enriched in N-CAM. As C2 cultures mature and differentiate, clusters persist at contacts between aligning myoblasts and between myotubes, consistent with a role in myogenesis. N- CAM is also enriched at cell-cell contacts in cultures of PC12, NRK, and CHO cells. These cells have significant amounts of N-CAM as detected on immunoblots. Clusters are not seen in L929 cells, which do not have detectable amounts of N-CAM. Coculture of these cells with C2 cells results in the clustering of N-CAM at heterologous contacts between C2 cells and NRK, CHO, or PC12 cells, but not between C2 cells and L929 cells. These results suggest that N-CAM specifically accumulates where N-CAM-bearing cells contact one another. Clustering of N-CAM may be an important step in strengthening intercellular adhesion.